Waste Animals Treatment Technology with All out System as an Effort to Improve Environmental Biosecurity, Livestock Health and Farmers Income in Activist Farm - Trisna, Ade; Purba, Mhd Adanan; Yunilas; Yusni, Eri (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2023)
"Activist Farm" is a sheep and goat farm that was established aimed at increasing the income of farmers and has the concept of integrating livestock whose target is to meet the protein needs of the community and the fulfillment of livestock seeds as a center for goat and sheep production in North Sumatra province. The limited knowledge and skills in raising livestock such us to procurement of feed ingredients, ration formulation and maintenance management encouraged coaching team from University of sumatera utara to provide assistance / coaches. Several technologies from research results of the university can be applied, so that they can motivated farmers to increase their business, increase farmer income and in order to support protein resilience during a pandemic. As a solution in overcoming this problem, it is necessary to increase knowledge and skills in the cultivation of goats, the introduction of alternative sources of feed ingredients (feed ingredients based on agricultural by-products, plantations, food processing industries) and livestock waste processing to support the productivity of goats to reduce production costs, making complete silage feed, making probiotics and formulating goat and sheep rations. The specific target of this activity is that farmers are able to determine potential alternative feed to be given for goats, are able to make probiotics for fermentation, complete fermentation and formulate rations, understand good farm management and efforts to improve biosecurity in supporting livestock health and the environment. The service method is packaged in the form of lectures, discussions, demonstrations, training and pilot projects. Service activities are summarized in a guidebook in the form of a Goat and Sheep Maintenance Management Module. From this activity, it is targeted that there will be cost efficiency (savings in animal feed costs because it can utilize alternative sources of feed ingredients), formulating and making independent concentrate feed, savings in the cost of purchasing probiotics and organic fertilizer fermentation methods.